GROUP DYNAMICS IN EMPOWERING HOUSEWIVES THROUGH KARAWO CRAFTS (World Bulletin of Social Sciences, 2022)
This study aims to determine the extent of the role of the housewife empowerment program in increasing karawo embroidery crafts in Dungingi sub-district. Karawo is a type of two-dimensional art decorative motif originating from Gorontalo. Karawo is a thread embroidery craft with certain motifs on the fabric that has been distributed. Karawo comes from the word "mokarawo" which is the native language of Gorontalo, which means to slice or make a hole. This research is a qualitative research with data collection methods through interviews and direct observation at one of the karawo craftsmen's houses located on Jalan Palma, Huangobotto Village, Dungingi District
Keywords: empowerment; karawo crafts; women